E-Module of Cube and Beam Based on Inquiry for Five Grade Students of Elementary School - Triwahyuningtyas, Dyah; Setiawan, Octavianus Yoga; Mahmuda, Novia Eka (Jurnal Prima Edukasia, 2022)
The background of this research is to produce and develop an e-module product of cube and block material centered on the approach. The teaching materials used printed books containing material and questions without any complex mathematical concepts so there is a lack of contextual learning in learning. That affects the lack of understanding of students' contextual knowledge during the geometry material pandemic. This study aims to develop an inquiry-based cube and block e-module for fifth-grade elementary students. Development research methods with 4D models include Definition, Design, Development, and Deployment. This research uses quantitative and qualitative data analysis techniques through media and material expert validators and teacher and student response questionnaires. The results showed that the inquiry-based cube and beam e-module was declared feasible or valid with an average score of 89.05%. Furthermore, e-modules through teacher and student response questionnaires obtained an average of 91.5%, which is very practical. Therefore, it influences students' cognition in understanding cube and block material with an average value of 84.1. Therefore, the inquiry-based cube and block e-module can help students improve their contextual abilities.